Editorial - Killingley, Dermot (Religions of South Asia, 2025)
This issue has only three articles, but they range from northeast to southwest, and from the sixth century to the present. Two of them are illustrated with photographs which are highly relevant to their subject matter and essential to their presentation. The unusual number of pictures made it difficult to include more articles.